Opening the Black Box : The Contextual Drivers of Social Accountability - Grandvoinnet, Helene; Aslam, Ghazia; Raha, Shomikho (Washington, DC: World Bank, 2015)
This publication fills an important knowledge gap by providing guidance on how to assess contextual drivers of social accountability effectiveness. It aims to strategically support citizen engagement at the country level and for a specific issue or problem.